ISLAMIC SCIENCE, NATURE AND HUMAN BEINGS: A DISCUSSION ON ZIAUDDIN SARDAR'S THOUGHTS - Masthuriyah Sa’dan (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
Currently the development of western science has been very advanced. However, the development of western science only concerns towards big profits without any consideration about the side effects of science development itself. The western science has marginalized the aspects of metaphysics and theology so that the western science arises materialistic characteristics for human beings, ecological damage, and disharmonic situations between nature and human. This writing discussed Ziauddin Sardar thoughts about Islamic science applying descriptive analysis approach. In Sardar’s thoughts, Muslim community must not follow western science; nevertheless, Muslim community may have Islamic science, having the Islamic characteristic and value. The characteristics of Islamic science cannot be separated from the ten parameters such as tawḥīd, khilāfah, ’ibādah, ’ilm, ḥalāl, ḥarām, ’adl, ẓulm, istiṣlāḥ and diyā’.